Conduct disorder in adolescent females: current state of research and study design of the FemNAT-CD consortium - Freitag, Christine M.; Herpertz, Sabine; Kieser, Meinhard (European child & adolescent psychiatry, 2018)
Conduct disorder (CD) is a common and highly impairing psychiatric disorder of childhood and adolescence that frequently leads to poor physical and mental health outcomes in adulthood. The prevalence of CD is substantially higher in males than females, and partly due to this, most research on this condition has used all-male or predominantly male samples. Although the number of females exhibiting CD has increased in recent decades, the majority of studies on neurobiological measures, neurocognitive phenotypes, and treatments for CD have focused on male subjects only, despite strong evidence for sex differences in the aetiology and neurobiology of CD. Here, we selectively review the existing literature on CD and related phenotypes in females, focusing in particular on sex differences in CD symptoms, patterns of psychiatric comorbidity, and callous-unemotional personality traits. We also consider studies investigating the neurobiology of CD in females, with a focus on studies using genetic, structural and functional neuroimaging, psychophysiological, and neuroendocrinological methods. We end the article by providing an overview of the study design of the FemNAT-CD consortium, an interdisciplinary, multi-level and multi-site study that explicitly focuses on CD in females, but which is also investigating sex differences in the causes, developmental course, and neurobiological correlates of CD.